Private equity-, stock- and mixed asset-portfolios: A bootstrap approach to determine performance characteristics, diversification benefits and optimal portfolio allocations - Daniel Schmidt (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
In this article, we investigate risk return characteristics and diversification benefits when private equity is used as a portfolio component. We use a unique dataset describing 642 US-American portfolio companies with 3620 private equity investments. Information about precisely dated cash flows at the company level enables for the first time a cash flow equivalent and simultaneous investment simulation in stocks, as well as the construction of stock portfolios for benchmarking purposes. With respect to the methodology involved, we construct private equity, stock-benchmark and mixed-asset portfolios using bootstrap simulations. For the late 1990s we find a dramatic increase in the extent to which private equity outperforms stock investment. In earlier years private equity was underperforming its stock benchmarks. Within the overall class of private equity, returns on earlier private equity investment categories, like venture capital, show on average higher variations and even higher rates of failure. It is in this category in particular that high average portfolio returns are generated solely by the ability to select a few extremely well performing companies, thus compensating for lost investments. There is a high marginal diversifiable risk reduction of about 80% when the portfolio size is increased to include 15 investments. When the portfolio size is increased from 15 to 200 there are few marginal risk diversification effects on the one hand, but a large increase in managing expenditure on the other, so that an actual average portfolio size between 20 and 28 investments seems to be well balanced. We provide empirical evidence that the non-diversifiable risk that a constrained investor, who is exclusively investing in private equity, has to hold exceeds that of constrained stock investors and also the market risk. From the viewpoint of unconstrained investors with complete investment freedom, risk can be optimally reduced by constructing mixed asset portfolios. According to the various private equity subcategories analyzed, there are big differences in optimal allocations to this asset class for minimizing mixed-asset portfolio variance or maximizing performance ratios. We observe optimal portfolio weightings to be between 3% and 65%.
urn:nbn:de:hebis:30-10631
Keywords: G11; 330; Venture Capital; Private Equity; Performance; Return; Risk; Portfolio; Fund; Diversification; Efficient Frontier; Allocation